Assessing vertical east-west bifacial photovoltaic systems in desert environments: Energy yield and soiling mitigation - Maulid Kivambe (19344709) (2024)
Desert environments exhibit high soiling rates that have a profound impact on the energy yield and the operations and maintenance of Photovoltaic (PV) power plants. This study investigates vertical east–west (Vertical) installation of bifacial PV modules in desert climates − its effectiveness in energy generation and as a mitigation strategy for PV soiling. To assess the impact of module bifaciality and orientation on energy yield and soiling, we compared the performance of latitude-tilted, i.e. 22° facing South (Tilted) bifacial and monofacial, and the vertical bifacial PV modules under real outdoor desert climatic conditions of Qatar. Our findings demonstrate that the vertical installation configuration presents an appealing alternative for energy production and holds great potential as a solution for mitigating soiling in desert climates. Over the study period, clean tilted bifacial modules produced approximately 4.0% more energy than clean vertical modules, on average. However, the tilted modules experienced substantial and progressive soiling losses, reaching up to 60% for monofacial modules. Although the losses for bifacial modules were also high, they were about 15% lower than those of monofacial modules. Additionally, during the summer months, when the sun’s path is higher in the sky, vertical bifacial modules generated 3.8% in average, and up to 9.2% more energy than the tilted modules. The results demonstrate that bifacial PV reduces the impact of PV soiling and the vertical module installation shows strong potential as an effective approach for energy production and combating PV module soiling in desert climates with high natural ground albedo. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2024.112835 Other institutions affiliated with: Bin Omran Trading & Telecommunication.